2006
DOI: 10.1159/000093096
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Double Bicanalicular Silicone Tubes after Endonasal Dacryocystorhinostomy in Lacrimal Canalicular Stenosis: A 10-Year Experience

Abstract: To assess the long-term results of double bicanalicular silicone tubes in canalicular (presaccal) stenosis of the nasolacrimal duct system, a retrospective follow-up was performed on patients operated between 1992 and 2002. Forty-five patients were included in the study, 44 of whom had eyes with canalicular stenosis (primary dacryocystorhinostomy), 4 with congenital agenesis of the lacrimal duct system, and 3 cases after primary external dacryocystorhinostomy. Double bicanalicular silicone tubes were inserted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
(16 reference statements)
2
12
0
Order By: Relevance
“…Tables 5 and 6 summarize the tuberelated complications in the present study and the complications associated with previous double silicone stenting studies. Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Tables 5 and 6 summarize the tuberelated complications in the present study and the complications associated with previous double silicone stenting studies. Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…In this report, a larger-diameter stent maintained a better separation of the lacrimal channel walls, which would be expected to decrease the chance of restenosis following stent removal. Similarly, double silicone tube stenting, as a method of widening dilation, has been suggested in several reports [12][13][14][15]; the clinical outcomes of these reports following double silicone tube intubation are summarized in Table 6. Two of them are cases with partial nasolacrimal duct obstruction (NLDO) or persistent congenital NLDO, and the patients received only double silicone intubation without DCR surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endoscopic technique was finally perfected over the years including an osteotomy between sac and nasal cavity (Wormald 2001;Tsirbas & Wormald 2003;Kim et al 2013). Canalicular silicone intubation at the end is widely favoured and used to prevent fibrous closure and sealing of the edges of the sac during healing (Yagci et al 1999;Caversaccio & Hausler 2006;Liang & Lane 2013). Studies have shown that the endoscopic DCR success percentages vary widely the last decades between 81% and as high as 97% in experienced hands (Tarbet & Custer 1995;Sprekelsen & Barberan 1996;Hartikainen et al 1998;Woog et al 2001;Durvasula & Gatland 2004;Tsirbas et al 2004;Ben Simon et al 2005;Leong et al 2010;Roithmann et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Caversaccio et al .,73 studied the results of double bicanalicular silicone tubes placed after endoscopic DCR in 44 patients with canalicular stenosis. They73 found that 32 (63%) of the patients became symptom-free 73.…”
Section: Canalicular Stenosismentioning
confidence: 99%